Non-financial disclosure and integrated reporting : practices and critical issues - Songini, Lucrezia,; Pistoni, Anna,; Baret, Pierre,; Kunc, Martin, (Studies in managerial and financial accounting ;, 2020)
The financial crisis of 2008 and its economic and social aftermath have highlighted the limits and risks of an increasingly global and embedded economy. Weakening society's trust in organizations and institutions, this has led to calls for new strategic paradigms that focus more on the ethical conduct of organizations. Performance measurement for sustainability and corporate social responsibility (CSR) plays a central role in these new contexts. The landscape of performance measurement and reporting is changing quickly, with calls for more integrated reporting and compulsory non-financial disclosures. Keeping up with those changes is a significant concern of managers in many organizations. Including research on the effectiveness and quality of non-financial disclosure, CSR/sustainability disclosure and Integrated Reporting, this exciting new volume looks to bridge the gaps in environmental, social and financial performance so managers can understand and successfully implement a broader, integrated view of performance measurement and reporting. Aimed at researchers and managers interested in performance measurement, this volume includes innovative research that sheds light on topics such as the determinants of disclosure quality, the identification of appropriate metrics, the relationship among the different disclosure mechanisms and between voluntary and mandatory disclosure, and many more.